OTHR-26. A pilot study of clinical minimal residual disease detection in pediatric embryonal brain tumors. (3rd June 2022) - Cole, Bonnie; Lockwood, Christina; Paulson, Vera; Lee, Amy; Hauptman, Jason; Goldstein, Hannah; Vitanza, Nicholas; Crotty, Erin; Leary, Sarah
Abstract: Cell-free DNA (cfDNA) presents an opportunity for measurement of minimal residual disease (MRD) in pediatric central nervous system (CNS) tumors. In this pilot study, we sought to evaluate the clinical use of low-pass whole genome sequencing (LP-WGS) of cfDNA in cerebrospinal fluid (CSF) of patients with embryonal neoplasms. 31 CSF samples were collected from 16 patients with molecularly characterized medulloblastoma (12), embryonal tumor with multilayer rosettes (2), and CNS embryonal tumors, NEC (2). Samples were collected at various treatment time points. Processing included centrifugation and freezing prior to cfDNA extraction, repair, adapter ligation, amplification, purification, and sequencing on an internally-developed and clinically-validated LP-WGS assay utilizing custom-developed bioinformatics and molecular pathologist review. 29 of 31 samples (94%) had adequate cfDNA in CSF for LP-WGS analysis. Copy number variants (CNVs) compatible with tumor were detected in 23 of 29 (79%) samples, including isodicentric chromosome 17, monosomy 6, MYCN amplification, and regional amplification of chromosome 19. In all cases with detectable cfDNA alterations in CSF, CNV were compatible with the molecular findings in tumor tissue. Two CSF samples had additional chromosomal alterations detected at the time of tumor progression that were not identified in the original tumors. All 9 lumbar puncture samples (100%) collected at initial staging had CSF cfDNA alterations indicative of MRD while corresponding cytologic evaluations of the same samples were positive in only 1 of 9 (11%). No MRD was detected in the single sample evaluated at the end of therapy time point. These findings suggest that LP-WGS of cfDNA in CSF represents a sensitive and clinically useful test for detection of MRD in patients with embryonal tumors of the CNS independent from CSF cytology. Future prospective studies are warranted to determine whether LP-WGS analysis of cfDNA in CSF can predict tumor recurrence and early treatment resistance in our patients.